Konsep Diri Muhajir Dalam Gaya Hidup Hijrah (Studi Kasus Pada Pria Dewasa Awal) - Izzah, Lailatul; Yuliza, Eva; Putri, Umi Hima (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
Early adulthood is a transitional period from adolescence. At this time the individual has begun to change values ​​that according to him are not by social expectations. Changes in views occur one of them regarding religious values. This process of change is also known as migration. During the migration process, the muhajir (the person who migrated) re-concepts himself with a new concept based on changes from the past and the new values ​​he follows. In this study, researchers used qualitative methods using case studies and collected data through semi-structured interview techniques. Sampling in this study used a non-random sampling technique, with purposive sampling, and obtained one subject with the initials "MGP", an early adult male who has a background in life with behavior violating religious teachings and is currently undergoing the process of migrating. The purpose of this research is to find out the description of the self-concept of a muhajir in his hijrah lifestyle. Based on the research results, it was found that MGP subjects were able to conceptualize themselves well and have a positive self-concept. Evidenced by the fulfillment of three aspects of self-concept, namely: knowledge, expectations, and assessment. The subject has hopes for the future by being useful to others and the subject is trying to do his best and the subject can be an judge for himself.